A Distinct Human CD4+ T Cell Subset That Secretes CXCL13 in Rheumatoid Synovium. Issue 12 (December 2013) - Kobayashi, Shio; Murata, Koichi; Shibuya, Hideyuki; Morita, Mami; Ishikawa, Masahiro; Furu, Moritoshi; Ito, Hiromu; Ito, Juichi; Matsuda, Shuichi; Watanabe, Takeshi; Yoshitomi, Hiroyuki
<x xml:space="preserve">Abstract</x> Objective A subset of CD4+ T cells in the synovium of patients with rheumatoid arthritis (RA) produce CXCL13, a chemokine that is crucial for the formation of germinal centers. This study was undertaken to determine the relevance of this population to known subsets of T helper cells and to proinflammatory cytokines, and how these cells are generated. Methods The expression of Th markers and CXCL13 by CD4+ T cells in RA synovium and the involvement of proinflammatory cytokines in CXCL13 production were assessed. We also investigated whether CXCL13+CD4+ T cells could be newly induced. Results CXCL13+CD4+ T cells in RA synovium were negative for interferon‐γ (IFNγ), interleukin‐4 (IL‐4), IL‐17, FoxP3, and CXCR5 and expressed low levels of inducible T cell costimulator, indicating that this population is a distinct human CD4 subset. T cell receptor (TCR) stimulation of CD4+ T cells, obtained from RA synovium with low expression of CXCL13, promptly induced CXCL13 production and addition of proinflammatory cytokines supported the long‐term production of CXCL13. These findings indicate that CXCL13‐producing CD4+ T cells can be in a memory state ready to be reactivated upon TCR stimulation and that proinflammatory cytokines are involved in persistent CXCL13 production. TCR stimulation of CD4+ T cells from the blood of healthy volunteers, together with proinflammatory cytokine supplementation, induced a population that produced CXCL13, but not IFNγ. Synovial T cells recruited CXCR5+ cells in a CXCL13‐dependent manner. Conclusion CXCL13‐producing CD4+ T cells induced in RA synovium may play a role in the recruitment of CXCR5+ cells, such as B cells and circulating follicular helper T cells, and in ectopic lymphoid neogenesis at sites of inflammation.